Stead Ellis, Architect - Marriage, Guy; Marriage, Robin; Bowman, Ian (Architectural History Aotearoa, 2013)
In December 1879, Stead Ellis landed in New Zealand, with family, seeking work as an architect in the South Island, along with his pupil, budding architect Joshua Charlesworth. Finding work in Nelson as the Architect for the Nelson Education Board in early 1880, Ellis was a key architect, along with Beatson, in the appearance of early Nelson’s public buildings. Ellis was responsible for designing many school buildings in the Nelson region, and also other commissions such as the church at Motupiko. Very little remains of Ellis’ lifetime of work, with most schools having replaced their buildings several times over, but some few scraps of Ellis’ work remain - namely two buildings: the Bishops School, near the Nelson Cathedral, and the Anglican church at Motupiko. This paper will examine and trace remaining work of Stead Ellis.